Pengaruh Kepemimpinan Transformasional, Kompetensi, Dan Motivasi Berprestasi Terhadap Kinerja Konsultan Pengawas Di PT. Eskapindo Matra - Bambang Priyo S. (Universitas Islam Kadiri, 2020)
This study aims to testing the influence of transformational leadership style, competence and achievement motivation on performance. This research is carried out at PT. Eskapindo Matra Kso PT. Dressa Cipta Engineering at the package of consultation services engineering supervision of the construction of the toll road Solo - Ngawi - Kertosono segment: Ngawi - Kertosono package 3. sta 118 + 700 - sta 139 + 760. The purpose of this study is to explain and further analyze the effect of transformational leadership style, competence and achievement motivation on the performance of supervision consultant personnel. The sample of this research is 82 person personnel of supervision consultant team of Solo - Ngawi toll road construction: Ngawi - Kertosono package 3. sta 118 + 700 - sta 139 + 760, data collection with census or saturated sampling technique. Data testing with SPSS 21.0 for validity and reliability test, classical assumption test and multiple regression analysis. The result of this research is that transformational leadership has no significant effect on performance, while competence has a positive and significant effect on performance as well as motivation have positive and significant effect to performance.